Tuberculosis diagnosis using immunodominant, secreted antigens of Mycobacterium tuberculosis - Bekmurzayeva, Aliya; Sypabekova, Marzhan; Kanayeva, Damira (Tuberculosis, 2013)
Summary Tuberculosis (TB) remains a major public health concern in most low-income countries. Hence, rapid and sensitive TB diagnostics play an important role in detecting and preventing the disease. In addition to established diagnostic methods, several new approaches have been reported. Some techniques are simple but time-consuming, while others require complex instrumentation. One prominent and readily available approach is to detect proteins that Mycobacterium tuberculosis secretes, such as Mpt64, the 6-kDa early secreted antigenic target (Esat6), the 10-kDa culture filtrate protein (Cfp10), and the antigen 85 (Ag85) complex. Although their functions are not fully understood, a growing body of molecular evidence implicates them in M. tuberculosis virulence. Currently these biomarkers are either being used or investigated for use in skin patch tests, biosensor analyses, and immunochromatographic, immunohistochemical, polymerase chain reaction-based, and enzyme-linked immunosorbent assays. This review provides a comprehensive discussion of the roles these immunodominant antigens play in M. tuberculosis pathogenesis and compares diagnostic methods based on the detection of these proteins with more established tests for TB.
Keywords: Tuberculosis diagnosis; Mpt64; Esat6; Cfp10; Ag85; Biosensor